Altered rhizoctonia assemblages in grasslands on ex-arable land support germination of mycorrhizal generalist, not specialist orchids - Vogt-Schilb, Hélène; Těšitelová, Tamara; Kotilínek, Milan; Sucháček, Pavel; Kohout, Petr; Jersáková, Jana (The New phytologist, 2020)
Species-rich seminatural grasslands in Central Europe have suffered a dramatic loss of biodiversity due to conversion to arable land, but vast areas are being restored. Population recovery of orchids, which depend on mycorrhizal fungi for germination, is however limited. We hypothesised that ploughing and fertilisation caused shifts in orchid mycorrhizal communities in soil and restricted orchid germination. We examined edaphic conditions in 60 restored and seminatural grasslands, and germination success in 10 restored grasslands. Using a newly designed primer, we screened the composition of rhizoctonias in soil, seedlings and roots of seven orchid species. Seminatural and restored grasslands differed significantly in nutrient amounts and rhizoctonia assemblages in soil. While Serendipitaceae prevailed in seminatural grasslands with a higher organic matter content, Ceratobasidiaceae were more frequent in phosphorus-rich restored grasslands with increased abundance on younger restored sites. Tulasnellaceae displayed no preference. Germination success in restored grasslands differed significantly between orchid species; two mycorrhizal generalist species germinated with a broad range of rhizoctonias at most restored grasslands, while germination success of specialists was low. Past agricultural practices have a long-lasting effect on soil conditions and orchid mycorrhizal communities. Altered mycorrhizal availability may be the main reason for low germination success of specialist orchid species.
Keywords: Mycorrhizae; orchid mycorrhizal fungi; Orchidaceae; secondary succession; specializace; klíčení; fungal community; Europe; high-throughput sequencing; Germination; protocorm; Grassland; Rhizoctonia; Evropa; phosphorus; seed germination; pastviny; Specialization; restored grassland; mykorhiza